Early Eocene Nummulitids from Gebel Umm Russeies, El Galala El Bahariya, Eastern Desert, Egypt - Boukhary, Mohamed (Array, 2009)
Summary: Seven larger foraminiferal species: Nummulites aff. nemkovi SCHAUB, 1966, Nummulites partschi DE LA HARPE, 1880, Nummulites bassiounii BOUKHARY & BLONDEAU, 1991, Nummulites cf. campesinus SCHAUB, 1966, Assilina aff. major HEIM, 1908, Decrouezina aegyptiaca Boukhary, 1994 and Operculina sp. are described from the Early Eocene Gebel Umm Russeies, Northern Galala, Eastern Desert, Egypt. These taxa are biostratigraphically evaluated and according to the standard shallow benthic zones, the identified biozones span SBZ 10 to SBZ 12 in the shallow benthic zones (SBZ) of SERRA-KIEL et al. (1998) which are assigned to the Late Ypresian